Pengetahuan, kesadaran dan sikap masyarakat terhadap air limbah rumah tangga di Kawasan Gegerkalong Girang - Asyah Dwi Hastika; Surtikanti, Hertien Koosbandiah (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Household wastewater is one of the causes of water pollution which has a major impact on the environment, health and water quality. This research aims to describe the impact of community knowledge, awareness and attitudes on the condition of household wastewater in the Gegerkalong Girang area. This research is qualitative research with an analytical survey method. Research data was collected using questionnaires and questionnaires and analyzed using literature studies. The research results show that community knowledge, awareness and attitudes have an impact on the condition of household wastewater. Pollution caused by household wastewater can be prevented by planning good and correct waste disposal and processing household wastewater.